Anti-glare laminate
By using a composition of a monomer with a multifunctional (meth)acryloyl group and a polymer with a (meth)acryloyl group, an anti-glare layer with high hardness and heat resistance and reduced glare, the problem of degradation of display performance and insufficient scratch resistance in the existing anti-glare layer is solved.
Patent Information
- Application Number
- CN202380052064.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-24
- Publication Date
- 2025-02-28
AI Technical Summary
When the existing anti-glare layer forms concave and convexity on the surface to prevent light from being reflected, it may lead to a degradation of the display performance of the display device, and the active ray-curing compound with high crosslinking is prone to cracks in the heating test and is insufficiently scratch-resistant.
A monomer containing a multifunctional (meth)acryloyl group, a polymer having a (meth)acryloyl group, a photopolymerization initiator and silica particles are used as the anti-glare layer. By adjusting the component ratio and particle size distribution, the hardness and heat resistance of the anti-glare layer are improved.
Effectively reduce glare, improve the hardness and heat resistance of the anti-glare layer, while ensuring high scratch resistance.
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to an anti-glare laminate. More specifically, the present invention relates to an anti-glare laminate having both anti-glare performance and high scratch resistance and substrate adhesion, and is used as a surface material for a vehicle-mounted liquid crystal display device or a mobile phone terminal, a personal computer, or a tablet PC, which has excellent anti-glare performance. Background Art
[0002] In a liquid crystal display device, an optical laminate for preventing reflection is usually provided on the outermost surface. This anti-reflection optical laminate suppresses image reflection and reduces reflectivity by scattering and interfering light.
[0003] As one of the optical laminates for anti-reflection, an anti-glare film having an anti-glare layer with a concavo-convex shape formed on the surface of a transparent substrate is known. This anti-glare film can scatter external light by utilizing the concavo-convex shape of the surface, thereby preventing the reduction of visibility caused by the reflection of external light and the reflection of the image. In addition, the optical laminate is usually provided on the outermost surface of the liquid crystal display device, so it is also necessary to impart hard coating properties to prevent scratches during operation.
[0004] On the display surface of liquid crystal display devices and organic electroluminescent (EL) display devices, a mixture of fine particles and a binder resin or a curable resin is usually coated on a substrate to form fine concave and convex surfaces to prevent specular reflection and prevent image reflection.
[0005] Patent Document 1 discloses, as a method for forming unevenness on a surface, a method of using dipentaerythritol hexaacrylate as a multifunctional acrylate and SYLYSIA 350 as silica particles in an antiglare layer.
[0006] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2009-66891 Summary of the invention
[0007] Problems to be solved by the invention When the surface is uneven, it can prevent the reflection of external light, but it may cause the display performance of the display device to deteriorate. In particular, when an anti-glare film is installed on the surface of a display device with high-definition pixels, the pixels of the display device may appear to be magnified due to the lens effect of the surface unevenness, etc., which may cause so-called glare.
[0008] In order to ensure the scratch resistance of the surface, the anti-glare layer usually uses an active ray-curable compound with a high degree of cross-linking. However, the high degree of cross-linking also increases the curing shrinkage, which may cause cracks in the heating test.
[0009] Therefore, an object of the present invention is to provide an anti-glare laminate that can not only suppress glare but also ensure the heat resistance of the anti-glare layer and have high scratch resistance.
[0010] Technical means to solve problems The inventors of the present invention have conducted intensive studies to solve the above-mentioned problems and have found that the above-mentioned problems can be solved by forming an anti-glare layer using a specific amount of a specific component. That is, the present invention is as follows.
[0011] <1> An anti-glare laminated body comprises at least a substrate layer and an anti-glare layer, wherein: The anti-glare layer contains at least a monomer (A) having a multifunctional (meth)acryloyl group, a polymer (B) having a (meth)acryloyl group, a photopolymerization initiator (C) and silica particles (D). The average particle size of the silica particles is 1 to 7 μm, and the oil absorption of the silica particles is 30 to 250 mL / 100 g. When the total of the above-mentioned components (A) and (B) is 100% by mass, the proportion of the component (A) is 40 to 90% by mass, and the proportion of the component (B) is 10 to 60% by mass. The double bond equivalent of the component (B) is 400 g / mol or less.
[0012] <2> According to the above <1> In the anti-glare laminate, the weight average molecular weight of the component (B) is 5,000 to 100,000.
[0013] <3> According to the above <1> or <2> In the anti-glare laminate, when the total of the components (A) and (B) is 100% by mass, the content of the component (D) is 1 to 20% by mass.
[0014] <4> According to the above <1> ~ <3> In any one of the anti-glare laminates, the substrate layer includes an aromatic polycarbonate layer.
[0015] <5> According to the above <1> ~ <4> In any one of the above anti-glare laminates, the substrate layer includes at least two layers, namely, an acrylic resin layer and an aromatic polycarbonate layer.
[0016] <6> According to the above <1> ~ <5> The anti-glare laminate according to any one of the preceding claims, further comprising an optical interference layer on the anti-glare layer.
[0017] <7> According to the above <1> ~ <6> The anti-glare laminate according to any one of the preceding claims has an adhesive layer on a surface of the substrate layer opposite to the anti-glare layer.
[0018] Effects of the Invention According to the present invention, in the anti-glare laminate, glare can be reduced, and the surface of the anti-glare layer can have high hardness and excellent heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 : is a cross-sectional view showing a specific example of an anti-glare laminate according to one embodiment of the present invention. Figure 1 The structure of the anti-glare laminate 10 of the laminate exemplified in FIG. 1 is composed of an anti-glare layer 12 , a polymethyl methacrylate layer (PMMA resin layer) 16 , and a polycarbonate layer (PC resin layer) 20 . DETAILED DESCRIPTION
[0020] The present invention will be described in detail below. However, the present invention is not limited to the following embodiments, and any changes can be made within the scope of the effects of the present invention.
[0021] The anti-glare laminate of the present invention comprises an anti-glare layer and a substrate layer. These layers are described below.
[0022] [Anti-glare layer] The anti-glare layer is formed by a composition comprising a monomer having a multifunctional (meth) acryloyl group, a polymer having a (meth) acryloyl group, a photopolymerization initiator and silicon dioxide particles. In order to further improve the function of the anti-glare layer, various additives may be included. The components that can be contained in the composition used as the raw material of the anti-glare layer are described below.
[0023] <Monomer Having a Polyfunctional (Meth) Acryloyl Group> The anti-glare layer contains a monomer having a multifunctional (meth)acryloyl group. The monomer having a multifunctional (meth)acryloyl group is cross-linked by polymerization, and the hardness of the anti-glare layer can be increased.
[0024] In the present invention, the monomer having a polyfunctional (meth)acryloyl group refers to a compound having two or more (meth)acryloyl groups. The monomer having a polyfunctional (meth)acryloyl group may be used alone or in combination of two or more.
[0025] Examples of the monomer having a polyfunctional (meth)acryloyl group include 1,6-hexanediol (meth)acrylate, 1,9-nonanediol (meth)acrylate, bisphenol A di(meth)acrylate, trimethylolpropyl tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0026] The monomer having a multifunctional (meth)acryloyl group may be oxyalkylene-modified or epoxy-modified. Oxyalkylene-modified or epoxy-modified monomers can suppress curing shrinkage during crosslinking and improve the heat resistance of the anti-glare layer.
[0027] The molecular weight of the monomer having a polyfunctional (meth)acryloyl group is preferably 1000 or less, more preferably 800 or less, and further preferably 600 or less. When the molecular weight exceeds 1000, the adhesion to the substrate may be reduced.
[0028] The hydroxyl value of the monomer having a polyfunctional (meth)acryloyl group is preferably 10 mgKOH / g or more, more preferably 30 mgKOH / g or more, and further preferably 50 mgKOH / g or more. If the hydroxyl value is less than 10 mgKOH / g, the dispersibility of the composition may be reduced.
[0029] When the total amount of the monomer having a multifunctional (meth) acryloyl group and the polymer having a (meth) acryloyl group is set to 100 mass %, the amount of the monomer having a multifunctional (meth) acryloyl group is 40 to 90 mass %, preferably 50 to 90 mass %, more preferably 55 to 85 mass %, and further preferably 60 to 80 mass %. When it is less than 40 mass %, the adhesion between the anti-glare layer and the substrate layer is reduced; when it exceeds 90 mass %, the heat resistance of the anti-glare layer is reduced.
[0030] <Polymer Having a (Meth)Acryloyl Group> The anti-glare layer contains a polymer having a (meth)acryloyl group. The polymer having a (meth)acryloyl group can suppress curing shrinkage caused by polymerization and improve heat resistance.
[0031] The polymer having a (meth)acryloyl group can be obtained, for example, by copolymerizing (meth)acrylic acid and (meth)acrylic acid glycidyl ether to synthesize an epoxy compound having a (meth)acrylate skeleton, and then adding acrylic acid or methacrylic acid to the epoxy compound. A synthesis example is shown below.
[0032] Examples of epoxy (meth)acrylate used for the polymer having a (meth)acryloyl group include compounds having a repeating unit represented by the following formula (I).
[0033] In formula (I), m is an alkylene group having 1 to 4 carbon atoms or a single bond, n is an alkyl group having 1 to 4 carbon atoms or hydrogen, p is a single bond or an alkylene group having 1 or 2 carbon atoms, and q is an alkyl group having a total carbon number of 1 to 12 or hydrogen which may contain at least one substituent selected from epoxy, hydroxyl, acryloyl and methacryloyl groups.
[0034] The epoxy (meth)acrylate polymer more preferably contains the following repeating units, that is, a repeating unit containing m in the above formula (I) is an alkylene group having 1 or 2 carbon atoms, n is an alkyl group having 1 or 2 carbon atoms, p is a single bond or a methylene group, and q is an alkyl group having a total carbon number of 1 to 6 or hydrogen which may contain at least one substituent selected from glycidyl group, hydroxyl group and acryloyl group.
[0035] For example, in the above formula (I), m is a methylene group, n is a methyl group, p is a single bond, and q is a methyl group, an alkyl group having 5 or less carbon atoms including a glycidyl group (epoxy group), an alkyl group having 8 or less carbon atoms including a hydroxyl group and an acryloyl group, or the like.
[0036] Specific examples of the repeating unit contained in the epoxy (meth)acrylate polymer include repeating units represented by the following formula (II-a), formula (II-b), and formula (II-c).
[0037] In the (meth)acrylate polymer, based on the total molar number of the repeating unit of the formula (II-a), the repeating unit of the formula (II-b) and the repeating unit of the formula (II-c), the repeating unit of the formula (II-a) is preferably 30 to 85 mol%, more preferably 40 to 80 mol%. Based on the total molar number, the repeating unit of the formula (II-b) is preferably 5 to 30 mol%, more preferably 10 to 25 mol%. Furthermore, based on the total molar number, the repeating unit of the formula (II-c) is preferably 10 to 40 mol%, more preferably 10 to 35 mol%.
[0038] The molar ratio of the repeating unit of the formula (II-a), the repeating unit of the formula (II-b), and the repeating unit of the formula (II-c) is preferably 4.5 to 5.5:1.5 to 2.5:2.5 to 3.5, for example, 5:2:3.
[0039] Such a polymer having a (meth)acryloyl group is sold as a commercial product and can be easily obtained. Examples thereof include SMP-220A (manufactured by Kyoeisha Chemical Co., Ltd.), SMP-250A (manufactured by Kyoeisha Chemical Co., Ltd.), SMP-360A (manufactured by Kyoeisha Chemical Co., Ltd.), SMP-550A (manufactured by Kyoeisha Chemical Co., Ltd.), HA7975 (manufactured by Showa Denko Materials Co., Ltd.), HA7975D (manufactured by Showa Denko Materials Co., Ltd.), RA-4101 (manufactured by Negami Industry Co., Ltd.), 8KX-078 (manufactured by Daisei Fine Chemicals Co., Ltd.), and 8KX-212 (manufactured by Daisei Fine Chemicals Co., Ltd.).
[0040] The double bond equivalent of the polymer having a (meth)acryloyl group is 400 g / mol or less, preferably 360 g / mol or less, and more preferably 250 g / mol or less. When it exceeds 400 g / mol, the hardness of the antiglare layer decreases.
[0041] The weight average molecular weight of the polymer having a (meth)acryloyl group is preferably 5000 to 100000, more preferably 10000 to 70000, and even more preferably 15000 to 50000. When it is less than 5000, the effect of inhibiting cure shrinkage may not be obtained, and when it exceeds 100000, the viscosity of the composition increases, and coating may become difficult.
[0042] When the total amount of the monomer having a multifunctional (meth) acryloyl group and the polymer having a (meth) acryloyl group is set to 100 mass %, the amount of the polymer having a (meth) acryloyl group is 10 to 60 mass %, preferably 10 to 50 mass %, more preferably 15 to 45 mass %, and further preferably 20 to 40 mass %. When it is less than 10 mass %, the heat resistance of the anti-glare layer is reduced; and when it exceeds 60 mass %, the adhesion between the anti-glare layer and the substrate layer is reduced.
[0043] The anti-glare layer contains silica particles, which form irregularities on the surface of the anti-glare layer, thereby providing an anti-glare effect.
[0044] As a method for producing silica particles, there are dry methods, wet methods, etc. Among them, the wet method is preferred from the viewpoint of the large number of silanol groups on the surface and the dispersibility with the resin.
[0045] The shape of the silica particles is not particularly limited, and examples thereof include spherical shapes and irregular shapes. Irregular shapes are more preferred because they can adhere firmly to the resin and improve the scratch resistance of the antiglare layer.
[0046] The average particle size of the silica particles is 1 to 7 μm, preferably 2 to 6 μm, and more preferably 3 to 5 μm. When the particle size is less than 1 μm, the anti-glare effect cannot be obtained; and when the particle size is greater than 7 μm, glare is easily generated. In the present invention, the average particle size of the silica particles can be measured by a laser diffraction method.
[0047] The oil absorption of the silica particles is 30 to 250 mL / 100 g, preferably 70 to 230 mL / 100 g, and more preferably 90 to 200 mL / 100 g. When the oil absorption is less than 30 mL / 100 g, the dispersibility in the resin is reduced; and when the oil absorption is more than 250 mL / 100 g, the anti-glare layer is prone to glare. In the present invention, the oil absorption of the silica particles can be measured according to JIS K5101.
[0048] Such silica particles are sold as commercial products and can be easily obtained. Examples thereof include SYLYSIA series, SYLOPHOBIC series, SYLOSPHERE series of Fuji Silicon Chemical Co., Ltd., Nipsil series, NIPGEL series of Tosoh Silicon Chemical Co., Ltd., SUNSPHERE series of AGC Si-Tech, REOLOSIL series of Tokuyama Co., Ltd., and AEROSIL series of NIPPON AEROSIL CO., LTD.
[0049] When the total amount of the monomer having a multifunctional (meth) acryloyl group and the polymer having a (meth) acryloyl group is set to 100 mass %, the amount of the silica particles is preferably 1 to 20 mass %, more preferably 3 to 18 mass %, and further preferably 5 to 15 mass %. When it is less than 1 mass %, the anti-glare effect may not be obtained; and when it is more than 20 mass %, the total light transmittance of the anti-glare laminate may be reduced or glare may be easily generated.
[0050] The anti-glare layer contains a photopolymerization initiator. As the photopolymerization initiator, Omnirad 184 (1-hydroxy-cyclohexyl-phenyl-ketone), Omnirad 1173 (2-hydroxy-2-methyl-1-phenyl-propane-1-one), Omnirad TPO (2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide), Omnirad 819 (bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide), Esacure ONE (oligo(2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone)) manufactured by IGM Resins BV can be used. Among them, Omnirad 184 and the like are preferably used as the photopolymerization initiator from the viewpoint of heat resistance.
[0051] In the anti-glare layer, based on the total weight of the anti-glare layer, preferably 1% by weight to 6% by weight of a photopolymerization initiator is contained. The content of the photopolymerization initiator in the anti-glare layer is more preferably 2% by weight to 5% by weight, and further preferably 3% by weight to 4% by weight.
[0052] In order to impart the anti-glare layer with scratch resistance and hardness, nanoparticles can be added. For example, nano silicon dioxide, nano aluminum oxide, nano titanium dioxide, nano zirconium oxide, etc. can be used. In addition, nano diamonds, etc. as organic particles can also be used. The nanoparticles contained in the anti-glare layer are preferably treated with a surface treatment agent. Through surface treatment, inorganic nanoparticles can be dispersed in a stable state in a composition, particularly in a polymer with a (meth)acryloyl group.
[0053] As the surface treatment agent for nanoparticles, it is suitable to use a substituent that can bond with the surface of the nanoparticles and a compound with a high compatibility with the components of the hard coating composition for dispersing the nanoparticles, particularly with a (meth)acryloyl polymer. For example, as the surface treatment agent, silane compounds, alcohols, amines, carboxylic acids, sulfonic acids, phosphonic acids, etc. can be used.
[0054] The nanoparticles preferably have copolymerizable groups on their surfaces. The copolymerizable groups can be introduced by surface treatment of the inorganic nanoparticles, and specific examples of the copolymerizable groups include vinyl groups, meth (acrylic acid) groups, free radical polymerizable groups, and the like.
[0055] The average particle size of the nanoparticles is preferably 5 to 500 nm, more preferably 10 to 300 nm, and even more preferably 20 to 100 nm. The average particle size of the nanoparticles is measured, for example, using a Zetasizer NanoZS from Malvern Panalytical by a particle size measurement method using a dynamic light scattering method.
[0056] As commercially available products of nanoparticles, for example, Snowtex series and organosilica sol series manufactured by Nissan Chemical Co., Ltd., and AdmaNano series manufactured by ADMATECHS COMPANY LIMITED can be used.
[0057] In order to impart leveling, antifouling and abrasion resistance to the antiglare layer, an organosilicon compound may be added. The organosilicon compound preferably uses a compound having a polyalkylsiloxane bond. These compounds may also be synthetic, but commercial products are easily available. For example, the KP series of Shin-Etsu Silicone Co., Ltd., the BYK series of BYK Chemical Japan Co., Ltd., and the TEGO Glide series of Evonik Corporation may be used.
[0058] In order to impart leveling, antifouling and abrasion resistance to the anti-glare layer, a fluorine compound may be added. Fluorine compounds preferably use compounds having perfluoropolyether bonds. These compounds may also use synthetic products, but commercial products are easily available. For example, the MEGAFACE RS series of DIC Corporation, the KY series of Shin-Etsu Chemical Co., Ltd., the Optool series of Daikin Corporation, etc. may be used.
[0059] In order to impart weather resistance to the antiglare layer, an ultraviolet absorber may be added. Examples of the ultraviolet absorber include benzophenone-based ultraviolet absorbers such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-dodecyloxybenzophenone, 2-hydroxy-4-octadecyloxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, and 2,2',4,4'-tetrahydroxybenzophenone, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)benzotriazole, Benzotriazole-based UV absorbers such as (2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, phenyl salicylate, benzoate-based UV absorbers such as 2,4-di-tert-butylphenyl-3,5-di-tert-butyl-4-hydroxybenzoate, 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, (2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine and other triazine-based ultraviolet absorbers, 2-[2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yl] methacrylate ethyl, 2-[2-(6-hydroxybenzo[1 ,3]dioxolan-5-yl)-2H-benzotriazol-5-yl] ethyl acrylate, 3-[2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yl] methacrylate propyl, 3-[2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yl] methacrylate propyl, 4-[2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yl] methacrylate butyl, 4-[2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yl] methacrylate butyl, 2-[2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yl] acrylate butyl,2-[2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yloxy] ethyl methacrylate, 2-[3-{2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yloxy] ethyl methacrylate, 2-[3-{2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yloxy] ethyl methacrylate, 4-[3-{2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yl}propionyloxy] butyl methacrylate, 4-[3-{2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yl}propionyloxy] butyl acrylate, 2-[3-{2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yl}propionyloxy] butyl acrylate 2-[3-{2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl methacrylate, 2-(methacryloyloxy)ethyl-2-(6-hydroxybenzo[1,3]dioxolan-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl acrylate, Sesamol-type benzotriazole ultraviolet absorbers such as 2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, 4-(methacryloyloxy)butyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, and 4-(acryloyloxy)butyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate. The content of the ultraviolet absorber in the antiglare layer is preferably 0 to 5% by mass, more preferably 0 to 3% by mass, and even more preferably 0 to 1% by mass. When it exceeds 5% by mass, UV curing may be hindered.
[0060] In order to impart weather resistance to the antiglare layer, a light stabilizer may be added. Examples of the light stabilizer include hindered amine light stabilizers such as bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, bis(2,2,6,6-tetramethylpiperidin-4-yl) sebacate, bis(1-undecanyloxy-2,2,2,6-tetramethylpiperidin-4-yl) carbonate, 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate, bis[2,2,6,6-tetramethyl-1-(octyloxy)piperidin-4-yl] sebacate, and bis[1,2,2,6,6-pentamethyl-4-piperidinyl] 2-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]-2-butylmalonate. The content of the photostabilizer in the antiglare layer is preferably 0 to 5% by mass, more preferably 0 to 3% by mass, and even more preferably 0 to 1% by mass. When it exceeds 5% by mass, UV curing may be hindered.
[0061] The diluent solvent used to prepare the anti-glare layer-forming composition is not particularly limited as long as it is a non-polymerizable solvent for adjusting the viscosity. With such a diluent solvent, the anti-glare layer-forming composition can be easily coated mainly on the transparent substrate layer.
[0062] Examples of the diluting solvent include toluene, xylene, ethyl acetate, propyl acetate, butyl acetate, methyl cellosolve, ethyl cellosolve, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, methanol, ethanol, isopropanol, butanol, diacetone alcohol, acetone, butanone, methyl isobutyl ketone, cyclohexanone, hexane, heptane, octane, decane, dodecane, propylene glycol monomethyl ether, and 3-methoxybutanol.
[0063] As a method for coating the anti-glare layer-forming composition on the substrate layer, a bar coating method, a gravure coating method, a die coating method, a dip coating method, a spray coating method, or the like can be used.
[0064] After the composition is applied, it is dried at a predetermined temperature. The drying temperature is preferably 30 to 150°C, more preferably 60 to 120°C. When the temperature is lower than 30°C, the organic solvent may remain and affect the physical properties of the anti-glare layer. When the temperature exceeds 150°C, the substrate layer may deform.
[0065] The thickness of the antiglare layer is preferably in the range of 1 μm to 30 μm, more preferably 2 μm to 20 μm, and further preferably 5 μm to 15 μm. When less than 1 μm, it is difficult to obtain the desired performance, while when exceeding 30 μm, warping and poor flexibility may occur.
[0066] [Base material layer] The substrate layer contains a thermoplastic resin. The type of thermoplastic resin is not particularly limited, and various resins such as polycarbonate (PC) resin, acrylic resin such as polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polyimide (PI), cycloolefin copolymer (COC), norbornene-containing resin, polyether sulfone, celluloid, and aromatic polyamide can be used. Among these options, the thermoplastic resin of the substrate layer preferably contains at least a polycarbonate resin. In addition, from the perspective of toughness and heat resistance, aromatic polycarbonate is preferably used.
[0067] The type of polycarbonate resin contained in the substrate layer is not particularly limited, as long as the main chain of the molecule contains a -[O-R-OCO]- unit containing a carbonate bond (R is an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and has a linear structure or a branched structure), preferably a polycarbonate having a bisphenol skeleton, and particularly preferably a polycarbonate having a bisphenol A skeleton or a bisphenol C skeleton. As the polycarbonate resin, a mixture or copolymer of bisphenol A and bisphenol C can be used. By using a bisphenol C-based polycarbonate resin, such as a polycarbonate resin of only bisphenol C, a polycarbonate resin of a mixture or copolymer of bisphenol C and bisphenol A, the hardness of the substrate layer can be increased.
[0068] The viscosity average molecular weight of the polycarbonate resin is preferably 15,000 to 40,000, more preferably 20,000 to 35,000, and even more preferably 22,500 to 25,000.
[0069] In addition, the acrylic resin contained in the substrate layer is not particularly limited, and examples thereof include homopolymers of various (meth)acrylates represented by polymethyl methacrylate (PMMA) and methyl methacrylate (MMA), copolymers of PMMA or MMA and one or more other monomers, and mixtures of these resins. Among them, (meth)acrylates containing a cyclic alkyl structure with low birefringence, low hygroscopicity, and excellent heat resistance are preferred. Examples of the above-mentioned (meth)acrylic resins include ACRYPET (manufactured by Mitsubishi Rayon Co., Ltd.), Delpet (manufactured by Asahi Kasei Chemicals Co., Ltd.), and Parapet (manufactured by Kuraray Co., Ltd.), but are not limited to these.
[0070] A double layer product containing a polycarbonate resin and the above-mentioned acrylic resin may also be used. In this case, an anti-glare layer is preferably provided on the acrylic resin side. By using a double layer product containing a polycarbonate resin and the above-mentioned acrylic resin, the surface hardness can be increased while the toughness of the substrate layer can be maintained.
[0071] In addition, the substrate layer may also contain additives as components other than the thermoplastic resin. For example, at least one additive selected from the group consisting of a heat stabilizer, an antioxidant, a flame retardant, a flame retardant aid, an ultraviolet absorber, a release agent, and a colorant. In addition, an antistatic agent, a fluorescent brightener, an antifogging agent, a fluidity improver, a plasticizer, a dispersant, an antibacterial agent, etc. may also be added to the substrate layer.
[0072] In the substrate layer, the thermoplastic resin preferably contains 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more. In addition, in the thermoplastic resin of the substrate layer, the polycarbonate resin preferably contains 80% by mass, more preferably 90% by mass or more, and particularly preferably 95% by mass or more.
[0073] [Optical interference layer] In a preferred embodiment of the present invention, an optical interference layer is provided on the anti-glare layer. The method for forming the optical interference layer is not particularly limited, and coating, vapor deposition, sputtering and other film-forming methods may be used.
[0074] As a material for forming by coating, a coating material containing hollow silica can be used. The thickness of the layer containing hollow silica is preferably 80 to 120 nm.
[0075] As a material for forming a film by vapor deposition or sputtering, a metal oxide can be used. As the metal oxide, SiO2, TiO2, Nb2O5, etc. can be used.
[0076] By alternately stacking low refractive index layers and high refractive index layers to form a layer with a film thickness of 200 to 300 nm, an optical interference effect can be obtained. SiON or SiO x The sealing layer is formed to improve the sealing performance.
[0077] [Adhesive layer] In a preferred embodiment of the present invention, an adhesive layer is provided on the surface of the substrate layer opposite to the anti-glare layer. The method for forming the adhesive layer is not particularly limited, and is preferably formed by a coating method. As the material of the adhesive layer, there is no particular restriction, and acrylic adhesives, silicone adhesives, and polyurethane adhesives, etc., can be used. The thickness of the adhesive layer is not particularly limited, and is preferably more than 10 μm, more preferably more than 25 μm, further preferably more than 35 μm, and can also be more than 40 μm. In addition, the thickness of the adhesive layer is preferably less than 70 μm, more preferably less than 60 μm. By setting it within the above range, more suitable bonding performance and bonding strength can be achieved.
[0078] [Protective film] In order to prevent the anti-glare layer from being damaged, a protective film may be pasted on the anti-glare layer after drying. The surface of the protective film in contact with the anti-glare layer has an adhesive surface with moderate adhesive force, which is pasted to the surface of the anti-glare layer. The protective film may have only a single adhesive layer, but is preferably a double-layer structure having a substrate and an adhesive layer. In the protective film with a double-layer structure, the adhesive surface of the adhesive layer is laminated on the anti-glare layer in a manner that contacts the anti-glare layer. The protective film may also be a multilayer structure that also includes layers other than the above-mentioned substrate and adhesive layer. In addition, the protective film may also be a single-layer structure, and even if it is a single-layer protective film, the adhesive surface as the side surface of the anti-glare layer also has moderate adhesive force.
[0079] The substrate of the protective film is preferably formed of a thermoplastic resin, and more preferably contains a polyolefin resin. As the polyolefin resin contained in the protective film, for example, polyethylene, polypropylene, etc. can be used, which can be a homopolymer or a copolymer. Among the polyolefin resins, polyethylene is preferred.
[0080] As polyethylene, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), very low-density polyethylene (VLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE) and the like can be used, and low-density polyethylene is preferred.
[0081] As the polyolefin copolymer, a copolymer of ethylene or propylene and a monomer copolymerizable with these can be used. Examples of the monomer copolymerizable with ethylene or propylene include α-olefins, styrenes, dienes, cyclic compounds, and oxygen atom-containing compounds.
[0082] As the above-mentioned α-olefins, 1-butene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc. can be mentioned. As the above-mentioned styrenes, styrene, 4-methylstyrene, 4-dimethylaminostyrene, etc. can be mentioned. As the above-mentioned dienes, 1,3-butadiene, 1,5-hexadiene, 1,4-hexadiene, 1,7-octadiene, etc. can be mentioned. As the above-mentioned cyclic compounds, norbornene, cyclopentene, etc. can be mentioned. As oxygen-containing compounds, hexenol, hexenoic acid, methyl octenoate, etc. can be mentioned. These copolymerizable monomers can be used alone or in combination of two or more. In addition, it can also be a copolymer of ethylene and propylene.
[0083] The copolymer may be any of alternating copolymerization, random copolymerization and block copolymerization.
[0084] In the polyolefin resin contained in the base material of the protective film, a small amount of a modified polyolefin resin modified with a carboxyl group-containing monomer such as acrylic acid, maleic acid, methacrylic acid, maleic anhydride, fumaric acid, itaconic acid, etc. may be contained. The modification can usually be achieved by copolymerization or graft modification.
[0085] In the base material of the protective film, based on the total weight of the base material, it is preferably contained 80% by weight or more of polyolefin resin, more preferably the base material contains 90% by weight or more of polyolefin resin, and further preferably contains 95% by weight or more of polyolefin resin.
[0086] The adhesive layer of the protective film is preferably formed from an elastomer or a thermoplastic resin. As the thermoplastic resin contained in the adhesive layer, polyolefin resins such as polypropylene and modified polyolefin can be cited. As the polyolefin resin contained in the masking film, for example, polyethylene, polypropylene, etc. can be used, and it can be a homopolymer or a copolymer. Among the polyolefin resins, polyethylene is preferred.
[0087] In the adhesive layer of the protective film, based on the total weight of the adhesive layer, it is preferably contained 80% by weight or more of an elastomer or a thermoplastic resin, more preferably contains 90% by weight or more of an elastomer or a thermoplastic resin, and further preferably contains 95% by weight or more of an elastomer or a thermoplastic resin.
[0088] In the antiglare laminate, the thickness of the protective film is preferably 10 μm to 100 μm, more preferably 20 μm to 80 μm.
[0089] Examples Hereinafter, examples are given to more specifically illustrate the present invention, but the present invention is not limited to the following examples and can be arbitrarily changed within the scope not deviating from the gist of the present invention.
[0090] <SW hardness> On the surface of the antiglare layer, #0000 steel wool is reciprocated 15 times under a pressure of 100 gf / cm 2 for a scratch test. Visually observe the degree of damage and evaluate it on a 10-grade scale. Record it as RANK1 to RANK10.
[0091] RANK1: No scratches (equivalent to inorganic glass) RANK2: 1 to 5 scratches RANK3: 6 to 10 scratches RANK4: 11 to 15 scratches RANK5: 16 to 20 scratches RANK6: 21 to 25 scratches RANK7: 26 to 30 scratches RANK8: 31 to 40 scratches RANK9: 41 or more scars (same as polymethacrylic acid) RANK10: 41 or more scratches (same as polycarbonate) <Pencil Hardness> The measurement was conducted under the conditions of JIS K 5600-5-4: 1999, and the number of the hardest pencil that did not cause any damage was defined as the pencil hardness.
[0092] <Fitness test> Evaluation was performed according to the evaluation method of JIS K5600-5-6: 1999. The adhesion of Examples and Comparative Examples classified as 0 was evaluated as "good", and the adhesion of Examples and Comparative Examples classified as 1 to 5 was evaluated as "poor".
[0093] <Heating test> The anti-glare laminate was immersed in boiling water for 30 minutes, and then visually evaluated for appearance. Examples and Comparative Examples with no change were evaluated as "good", and those with change were evaluated as "poor".
[0094] <Haze> Evaluation was performed using a haze meter "HM-150" manufactured by Murakami Color Co., Ltd. in accordance with JIS K 7136:2000.
[0095] <Oil absorption> The measurement was conducted in accordance with JIS K 5101 using "Linseed Oil" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.
[0096] <Glare> The anti-glare laminate was placed on an iPad 6 with 265 ppi displaying green (R: 29, G: 205, B: 0) with the anti-glare layer facing upward, and the degree of glare was visually observed and evaluated according to the following criteria.
[0097] A: Almost no glare B: Glare is visible but does not affect practicality C: Visible glare that affects practicality Preparation Example 1 50% by mass of DPE-6A (monomer having hexafunctional acryloyl groups, manufactured by Kyoeisha Chemical Co., Ltd.), 50% by mass of SMP-220A (polymer having acryloyl groups, double bond equivalent of 220 g / mol, manufactured by Kyoeisha Chemical Co., Ltd.), 3% by mass of Omnirad184 (photopolymerization initiator, manufactured by IGM Resins BV), and 7% by mass of SYLYSIA 430 (silica particles, average particle size of 4.1 μm, oil absorption of 230 mL / 100 g, manufactured by Fuji Silicon Chemical Co., Ltd.) were diluted with propylene glycol monoethyl ether to a solid content concentration of 40% by mass, and stirred with a homogenizer for 10 minutes to obtain a mixed solution.
[0098] (Example 1) A two-layer product DF02U (manufactured by Mitsubishi Gas Chemical Co., Ltd., thickness 0.180 mm) of bisphenol A polycarbonate and PMMA was used as a substrate, and the mixed solution obtained in Preparation Example 1 was applied to the PMMA side using a bar coater so that the film thickness after drying was 10 μm, and then dried in an oven at 70° C. for 2 minutes. Then, UV curing was performed using a UV irradiator manufactured by Heraeus in a nitrogen environment in such a way that the accumulated light amount reached 400 mJ to obtain an anti-glare laminate.
[0099] (Example 2) An antiglare laminate was produced in the same manner as in Example 1 except that SYLYSIA 550 (silicon dioxide particles, average particle size 3.9 μm, oil absorption 160 mL / 100 g, manufactured by Fuji Silicon Chemical Co., Ltd.) was used instead of SYLYSIA 430 of Preparation Example 1.
[0100] (Example 3) An antiglare laminate was produced in the same manner as in Example 1 except that SYLYSIA 730 (silicon dioxide particles, average particle size 4.0 μm, oil absorption 95 mL / 100 g, manufactured by Fuji Silicon Chemical Co., Ltd.) was used instead of SYLYSIA 430 of Preparation Example 1.
[0101] (Example 4) An antiglare laminate was produced in the same manner as in Example 1 except that SYLOPHOBIC 200 (silicon dioxide particles, average particle size 3.9 μm, oil absorption 230 mL / 100 g, manufactured by Fuji Silysia Chemical Co., Ltd.) was used instead of SYLYSIA 430 of Preparation Example 1.
[0102] (Example 5) An antiglare laminate was produced in the same manner as in Example 1 except that 20SM-C11 (silica particles, average particle size 2.0 μm, oil absorption 35 mL / 100 g, manufactured by Admatechs) was used instead of SYLYSIA 430 of Preparation Example 1.
[0103] (Example 6) An anti-glare laminate was produced in the same manner as in Example 1, except that DPE-6A of Preparation Example 1 was changed to 65 mass %, SMP-220A was changed to 35 mass %, and SYLYSIA 550 was used instead of SYLYSIA 430.
[0104] (Example 7) An anti-glare laminate was produced in the same manner as in Example 1, except that DPE-6A of Preparation Example 1 was changed to 70 mass %, SMP-220A was changed to 30 mass %, and SYLYSIA 550 was used instead of SYLYSIA 430.
[0105] (Example 8) An anti-glare laminate was produced in the same manner as in Example 1 except that SMP-250A (polymer having an acrylic group, double bond equivalent of 360 g / mol, manufactured by Kyoeisha Chemical Co., Ltd.) was used instead of SMP-220A of Preparation Example 1 and SYLYSIA 550 was used instead of SYLYSIA 430.
[0106] (Example 9) An anti-glare laminate was produced in the same manner as in Example 1 except that SMP-360A (polymer having an acrylic group, double bond equivalent of 360 g / mol, manufactured by Kyoeisha Chemical Co., Ltd.) was used instead of SMP-220A of Preparation Example 1 and SYLYSIA 550 was used instead of SYLYSIA 430.
[0107] (Example 10) An antiglare laminate was produced in the same manner as in Example 1 except that PE-3A (a monomer having a trifunctional acryloyl group, manufactured by Kyoeisha Chemical Co., Ltd.) was used instead of DPE-6A of Preparation Example 1 and SYLYSIA 550 was used instead of SYLYSIA 430.
[0108] (Example 11) An antiglare laminate was produced in the same manner as in Example 1 except that PE-4A (monomer having tetrafunctional acryloyl groups, manufactured by Kyoeisha Chemical Co., Ltd.) was used instead of DPE-6A of Preparation Example 1 and SYLYSIA 550 was used instead of SYLYSIA 430.
[0109] (Comparative Example 1) An antiglare laminate was produced in the same manner as in Example 1 except that SYLYSIA 350 (silicon dioxide particles, average particle size 3.9 μm, oil absorption 320 mL / 100 g, manufactured by Fuji Silysia Chemical Co., Ltd.) was used instead of SYLYSIA 430 of Preparation Example 1.
[0110] (Comparative Example 2) An antiglare laminate was produced in the same manner as in Example 1 except that SUNSPHERE H-33 (silica particles, average particle size 3.0 μm, oil absorption 400 mL / 100 g, manufactured by AGC Si-Tech) was used instead of SYLYSIA 430 of Preparation Example 1.
[0111] (Comparative Example 3) An antiglare laminate was produced in the same manner as in Example 1 except that Nipsil E-1011 (silicon dioxide particles, average particle size 4.2 μm, oil absorption 350 mL / 100 g, manufactured by Tosoh Silicon Chemicals Co., Ltd.) was used instead of SYLYSIA 430 of Preparation Example 1.
[0112] (Comparative Example 4) An antiglare laminate was produced in the same manner as in Example 1 except that Nipsil E-1009 (silicon dioxide particles, average particle size 5.6 μm, oil absorption 350 mL / 100 g, manufactured by Tosoh Silicon Chemicals Co., Ltd.) was used instead of SYLYSIA 430 of Preparation Example 1.
[0113] (Comparative Example 5) An anti-glare laminate was produced in the same manner as in Example 1 except that the DPE-6A of Preparation Example 1 was changed to 25% by mass and the SMP-220A was changed to 75% by mass.
[0114] (Comparative Example 6) An anti-glare laminate was produced in the same manner as in Example 1 except that DPE-6A of Preparation Example 1 was set to 0 mass % and SMP-220A was set to 100 mass %.
[0115] (Comparative Example 7) An anti-glare laminate was produced in the same manner as in Example 1 except that DPE-6A of Preparation Example 1 was set to 100% by mass and SMP-220A was set to 0% by mass.
[0116] (Comparative Example 8) An anti-glare laminate was produced in the same manner as in Example 1 except that SMP-550A (polymer having an acrylic group, double bond equivalent of 550 g / mol, manufactured by Kyoeisha Chemical Co., Ltd.) was used instead of SMP-220A in Preparation Example 1.
[0117] The evaluation results of the anti-glare laminated bodies obtained in Examples 1 to 11 and Comparative Examples 1 to 8 are shown in Tables 1 and 2 below.
[0118] [Table 1] [Table 2]
Claims
1. An anti-glare laminate, characterized in that: The anti-glare laminate comprises at least a substrate layer and an anti-glare layer. The anti-glare layer at least comprises a monomer A having a multifunctional (meth)acryloyl group, a polymer B having a (meth)acryloyl group, a photopolymerization initiator C and silica particles D. The average particle size of the silica particles is 1 to 7 μm, and the oil absorption of the silica particles is 30 to 250 mL / 100 g. When the total amount of the above-mentioned component A and component B is 100 mass %, the proportion of the component A is 40 to 90 mass %, and the proportion of the component B is 10 to 60 mass %. The double bond equivalent of the component B is 400 g / mol or less.
2. The anti-glare laminate according to claim 1, wherein The weight average molecular weight of the component B is 5,000 to 100,000.
3. The anti-glare laminate according to claim 1 or 2, characterized in that: When the total of the above-mentioned components A and B is 100% by mass, the content of the component (D) is 1 to 20% by mass.
4. The anti-glare laminate according to any one of claims 1 to 3, wherein The substrate layer includes an aromatic polycarbonate layer.
5. The anti-glare laminate according to any one of claims 1 to 4, wherein The substrate layer includes at least two layers: an acrylic resin layer and an aromatic polycarbonate layer.
6. The anti-glare laminate according to any one of claims 1 to 5, wherein An optical interference layer is provided on the anti-glare layer.
7. The anti-glare laminate according to any one of claims 1 to 6, wherein The substrate layer has an adhesive layer on the surface opposite to the anti-glare layer.
Citation Information
Patent Citations
Anti-static and Anti-glare hard coat film and its production process
JP2009066891A